Determination of Immunobiological Reaction in Sheep Chlamydiosis - Navruzov N.I; Sayfidinov B.F; Aktamov U.B (International Journal on Orange Technologies, 2023)
The article reports on the stability of the immune system in the body when using the GOA formalin vaccine against sheep chlamydiosis.